173k views
2 votes
Helpppppppppppppppppppppppp

Helpppppppppppppppppppppppp-example-1
Helpppppppppppppppppppppppp-example-1
Helpppppppppppppppppppppppp-example-2
User Imox
by
5.4k points

1 Answer

5 votes
The first thing to is factor the denominator of the rational function:

x^(2) -2x-3 to do this we'll need to find two number whose product is -3 and its sum is -2; those numbers are 1 and -3, so:

x^(2) -2x-3=(x+1)(x-3)
Now we can rewrite our rational function as follows:

f(x)= (x-3)/((x+1)(x-3))
Notice that we have a common factor (x-3) in both numerator and denominator; therefore we can cancel them:

f(x)= (1)/(x+1)

Taking all the above into consideration we realize that x=3 is a removable discontinuity; the correct answer is the first one: there is a hole in x=3 and asymptote at x=-1.

User Xpusostomos
by
5.7k points